2012
DOI: 10.3347/kjp.2012.50.4.301
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Murine Fascioliasis Derives Early Immune Suppression with Increased Levels of TGF-β and IL-4

Abstract: In fascioliasis, T-helper 2 (Th2) responses predominate, while little is known regarding early immune phenomenon. We herein analyzed early immunophenotype changes of BALB/c, C57BL/6, and C3H/He mice experimentally infected with 5 Fasciola hepatica metacercariae. A remarkable expansion of CD19+ B cells was observed as early as week 1 post-infection while CD4+/CD8+ T cells were down-regulated. Accumulation of Mac1+ cells with time after infection correlated well with splenomegaly of all mice strains tested. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…TGF-β is secreted by regulatory T(Treg) cells, down-regulating the immune system after activation in response to allergens and pathogens [39]. In a previous study, mice serum levels of TGF-β were found to be increased after infection of Fasciola hepatica [40]. In this study, the concentrations of serum IL-4 and TGF-β in the immunized group and the infection group were both increased after L3 challenge, the concentrations in the nonimmunized and uninfected group (group 3) were still lower even when they were injected with adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β is secreted by regulatory T(Treg) cells, down-regulating the immune system after activation in response to allergens and pathogens [39]. In a previous study, mice serum levels of TGF-β were found to be increased after infection of Fasciola hepatica [40]. In this study, the concentrations of serum IL-4 and TGF-β in the immunized group and the infection group were both increased after L3 challenge, the concentrations in the nonimmunized and uninfected group (group 3) were still lower even when they were injected with adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…The kinetics of B‐cells in both infected and vaccinated animals would suggest that they play a role in providing protection. Chung, Bae, Yun, Yang, and Kong () noted an accumulation of splenic CD19 + B‐cells post‐infection in mice. Zafra et al.…”
Section: Immunity To Fasciola Sppmentioning
confidence: 99%
“…They play a crucial role in B-cell activation and have the unique capacity to bind and retain native antigen in B-cell follicles for long periods of time [13,14]. In previous papers, it has been reported that F. hepatica is able to downregulate the Th1 immune response and upregulate the Th2 response at early stages of infection in sheep [15] and mice [16], as well as in chronic stages in cattle [17]. This imbalance towards a Th2 immune profile is mediated through regulatory cytokines and cells, such as DC, that modulate and/or suppress inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%